Draw-A-Person with A Story (DAP-S) Test and Children with Learning Difficulties - Rosa, Helena Rinaldi; Migliorini, Walter José Martins [UNESP]; Da Silva, Marlene Alves; Manhani, Giulia Burgos (Instituto Brasileiro de Avaliacao Psicologica (IBAP), 2021)
Learning disabilities (LD) represent a challenge for the educational, social and health fields. The aim was to evaluate the applicability of the Draw-A-Person with a Story (DAP-S) test considering the understanding of children with learning disabilities. Twenty children from the third grade of a Public Elementary School in São Paulo-SP, identified by the school coordination as suffering some type of LD were individually evaluated. Their drawings were analyzed according to the emotional indicators (EI) and maturational indicators (MI) proposed by Koppitz and also through the free inspection method of the projective (graphic/narrative) material. The mean for the MI was lower, and the mean for the EI was higher than the result expected for the age. The correlation between the indicators was inverse and significant, although moderate. The DAP-S contributed to a singular understanding of children with LD and made it possible to raise hypotheses about the reasons for their difficulties, clarifying the data provided by the MI and EI.
O Desenho da Figura Humana com História (DFH-H) e Crianças com Dificuldades de Aprendizagem
Keywords: Dap-S; Human figure drawing; KOPPITZ; Learning difficulties; Psychological evaluation